Diagnostic value of functional tests in determining the condition of the cardiorespiratory system - M. Ben Otmen; Yu.M. Nechytailo (Zaslavsky O.Yu., 2022)
Background. The purpose was to study the nature of changes in the cardiorespiratory system in the case of short-term hypoxemia during functional tests with breath-holding. Materials and methods. The paper presents the results of a survey of school-age children with acute bronchitis with and without obstructive syndrome (60 patients) and a group of healthy children (52 people). Patients underwent pulse oximetry in combination with hypoxic tests for breath-holding with data recording on a computer and performed a Rufier test. Results. The severity of bronchitis in patients in the first days was average on the BSS-ped scale - 7.79 ± 0.19 points. The level of blood oxygen saturation was normal (above 95 %), but there was a difference between the groups: in patients with obstructive syndrome it was 98.60 ± 0.04 %, in the absence of this syndrome - 98.80 ± 0.03 %, which was lower than in the control group - 99.00 ± 0.01 % (p < 0.05). Time of breath-holding did not differ significantly between groups, but there was a slight decrease in saturation after them. There was greater reaction to breath-holding on exhalation. Level of oxygenation in patients with bronchitis achieved by increasing heart rate. Due to the phenomena of relative hypoxemia of peripheral tissues during convalescence, there was a decrease in tolerance to physical loading after the Rufier test. Conclusions. It is established that even in mild forms of acute bronchitis in children, according to functional tests, there is a decrease in gas exchange reserves, especially in the presence of obstructive syndrome. Compensatory mechanisms to maintain blood saturation are based on increasing systemic blood flow due to increased heart rate.